1982
DOI: 10.1148/radiology.142.1.7053523
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography of the anterior mediastinum in myasthenia gravis. A radiologic-pathologic correlative study.

Abstract: Chest radiographs and computed tomographic (CT) scans of the mediastinum were correlated with pathologic findings of the thymus following thymectomy in 57 patients with myasthenia gravis. Based on the patient's age and the overall morphology of the anterior mediastinum, CT scans were assigned one of four grades in an attempt to predict thymus pathologic findings. Using this grading, 14 of 16 cases of thymoma were suspected or definitely diagnosed. One of the two cases not diagnosed on CT was a microscopic tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
2

Year Published

1983
1983
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(9 citation statements)
references
References 0 publications
1
6
0
2
Order By: Relevance
“…However CT scan displayed only a small advantage over CXR or tomography at the hilum as has been found for other tumours within the chest (Fong et al, 1982;Muhm et al, 1979;Osbourne et al, 1982;Underwood et al, 1979;Baron et al, 1981). The low incidence of pericardial and pleural infiltration reflects the early stage in the disease at which most of these patients had been diagnosed.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…However CT scan displayed only a small advantage over CXR or tomography at the hilum as has been found for other tumours within the chest (Fong et al, 1982;Muhm et al, 1979;Osbourne et al, 1982;Underwood et al, 1979;Baron et al, 1981). The low incidence of pericardial and pleural infiltration reflects the early stage in the disease at which most of these patients had been diagnosed.…”
Section: Resultsmentioning
confidence: 90%
“…CT has been found to detect more mediastinal and pulmonary disease (Fong et al, 1982;Muhm et al, 1979;Osbourne et al, 1982;Underwood et al, 1979) in patients with thymoma and bronchial carcinoma, and it has been suggested that it may improve the staging of intrathoracic lymphoma (Ellert & Kreel, 1980). Comparison has not previously been made with conventional radiography, therefore a prospective study was undertaken to determine the role of thoracic CT in the management of patients with lymphoma.…”
mentioning
confidence: 99%
“…Pathologically, thymoma can be classified as Non-invasive (benign) or invasive (malignant) thymoma. Only about one-third of thymoma is malignant which is characterized by invasion of tumor into mediastinal fat and mediastinal structures rather than the basis of histological 9 . On CT scan, Thymoma can be visualized as a well-defined homogenous or heterogeneous attenuation depending on the presence of hemorrhage, necrosis or cyst formation 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies assessing the thymus often included patients with thymic hyperplasia or thymic carcinoma and did not provide statistical analysis for the thymoma patients alone; they usually compared these tumors by the WHO classification system rather than by the Masaoka-Koga staging system used in the clinical setting. [33][34][35][36][37][38] To improve our preoperative staging of thymoma, there have been attempts to study the morphology of the primary tumor as it compares with Masaoka staging. [39][40][41] In 2 retrospective studies assessing 50 and 58 patients with thymoma, 40,41 the authors tried to distinguish stage I thymoma from more advanced disease (stages II to IV) and found that partial or complete obliteration of fat planes around the tumor was not helpful in distinguishing stage I from higher stages.…”
Section: Ctmentioning
confidence: 99%